Pregnancy and myelodysplastic syndrome: an analysis of the clinical characteristics, maternal and fetal outcomes. (12th December 2015) - Yang, Zhang; Mei-Ying, Liang; Shan-Mi, Wang; Xiao-Hui, Zhang
Abstract: Objective : To investigate the clinical characteristics, management, maternal and fetal outcomes in pregnant patients with myelodysplastic syndrome (MDS). Methods : A retrospective analysis was conducted on 25 pregnant women with MDS between June 1998 and January 2013. The clinical data were summarized. These patients were divided into poor outcome group and control group, and regression analysis was conducted to find the risk factors for maternal and fetal outcomes. Results : Five patients developed premature birth, five patients developed postpartum hemorrhage, one patient developed postpartum acute cardiac failure and one patient developed postpartum cerebral infarction. Twenty out of the 25 patients underwent complete follow-up and 17 newborns were normal during follow-up. The regression analysis shows anemia and gestational hypertension are the primary risk factors for poor outcomes, whereas age, first onset of hematological disease, WBC count and platelet count are not significantly associated with the outcomes. Discussion : Anemia and gestational hypertension may be the primary risk factors for poor maternal and fetal outcomes in pregnant patients with MDS. To avoid maternal and neonatal complications, a minimum of hemoglobin level >70 g/L, platelet count >30 × 10 9 /L and WBC count >3 × 10 9 /L, are recommended. Close monitoring on blood routine, maternal complications and active supportive treatment are recommended.